Reliability and repeatability of 2021 ARCO classification and its guiding significance in treatment of nontraumatic osteonecrosis of the femoral head - Ju’an Yue; Xiaozhong Guo; Randong Wang; Bing Li; Qiang Sun; Wangyan Liu; Jiao Chen; Fengnian Zhao (BMC Musculoskeletal Disorders, 2023)
Abstract Background The study was designed to evaluate the interobserver reliability and intraobserver repeatability of the 2021 Association Research Circulation Osseous (ARCO) classification and explore its guiding significance in the treatment of nontraumatic osteonecrosis of the femoral head (ONFH). Methods In this retrospective study, we randomly selected and investigated 50 sets of preoperative computed tomography or magnetic resonance imaging scans from 96 patients (139 hips) to validate the reliability and repeatability of the 2021 ARCO classification. Patients with a nano-hydroxyapatite/polyamide-66 support rod were included in the clinical efficacy study. The Harris hip score (HHS) was used to assess hip function. Femoral head collapse of > 2 mm was considered radiological failure. Total hip arthroplasty (THA) was performed for clinical failure, and follow-up was discontinued. Results The average kappa value of interobserver consistency was 0.652. The average rate of consistency was 90.25%, and the average kappa value of intraobserver consistency was 0.836. Eighty-two patients (122 hips) were enrolled and followed up for a mean of 43.57 ± 9.64 months. There was no significant difference in the HHS among the three groups before surgery, but the difference was statistically significant at the last follow-up. Among them, types 1 and 2 had significantly higher scores at the last follow-up than preoperatively (P < 0.05), whereas type 3 had a lower score at the last follow-up than preoperatively, although the difference was not statistically significant (P > 0.05).According to the imaging evaluation, the failure rate of type 1, 2, and 3 at the last follow-up was 0%, 19%, and 87%, respectively. Univariate analysis showed that the femoral head survival rate of radiography was significantly affected by the new classification system (P = 0.00). At the last follow-up, the incidence rate of THA in type 1, 2, and 3 was 5%, 7%, and 31%, respectively. Univariate analysis showed that the femoral head survival rate was significantly affected by the new classification system (P = 0.001). Conclusions The 2021 ARCO classification for early-stage ONFH shows substantial consistency and repeatability. We do not recommend femoral head-preserving surgery for patients with type 3 ONFH.